Women’s continuous learning in the workplace - Tara, Fenwick (Adult Education Research Conference, 1996)
My study begins to explore the working-learning of women who describe themselves as "continuous learners". A major initial finding suggests that women’s workplace learnings intersect at three dimensions: (1) the intentions of the woman at a particular time in a particular community; (2) the disjuncture between the woman’s previous biography of experience and the situation immediately confronting her; and (3) the positionality of how a woman construes herself as a knowledge creator in relation to the object of knowing and the general knowledge community in which her learning is entwined. Overall, my findings suggest that the workplace is potentially rich with developmental possibilities, when an individual exercises autonomy and creativity in naming what is worth doing, what is valuable knowledge, and what is her idiosyncratic way of constructing this knowledge.